O encouraçado ético: Sergei Eisenstein e Pier Paolo Pasolini na crítica da forma jurídica capitalista - Xavier, Bruno Gadelha (2019)
The present work has as main objective a relation between Law and Cinema to critique the character of social exclusion propitiated by the capitalist economic system. To do so, we chose two film directors who will be defended as theoretical matrices suitable for criticism of the capitalist legal form, Sergei Eisenstein and Pier Paolo Pasolini. The central hypothesis of the work is that the prism demonstrated by the two theorists presents us with a method to critique the class character of the right of formative matrix eurocentric and bourgeois. In this scenario, the debate will be intermediated by Bioethics, here recognized from its perspective that we will call "(Bio) Ethics of the Common", with the consequent rupture of some models that do not correspond to a historical-dialectical materialist concern in search of "Communist Hypothesis ". The Marxist scenario will be present throughout the work, in order to emphasize that Eisenstein's “Intellectual Montage” and Pasolini's "The Written Language of Reality" present us with criticisms of the context of Law as belonging to the yearnings and determinations of the class that concentrates ownership in capitalist society. Thus, the theoretical corpus of each author will be analyzed, respecting not only a debate about art, but also the knowledge produced in the cinematographic field, with consequent analysis of the following films: "Strike", "Battleship Potemkin", "Accattone" , "The Gospel according to St. Matheus", "Salò: 120 days of Sodom". Once this structure is fixed in the first three chapters, we will begin a debate about the impact of the methods studied here in Brazilian cinema, indicating the influences and possibility of social rupture from the cinematic lens of Glauber Rocha, when we will analyze "God and the Devil in the Land of the Sun ".